THU0422 ICG-enhanced fluorescence optical imaging reveals subclinical disease activity in rheumatoid and psoriatic arthritis patients who have achieved clinical remission. (23rd January 2014) - Spiecker, F.; Werner, S.G.; Hermsen, C.; Bahner, M.; Backhaus, M.; Langer, H.-E.
Abstract : Background: Both MRI and ultrasonography (US) detect subclinical disease activity in most remission and low disease activity patients with rheumatoid arthritis (RA) (1, 2). Fluorescence optical imaging (FOI) has been shown to be not only a sensitive detector of synovitis (3), but also a useful tool in assessing treatment response in patients with RA and psoriatic arthritis (PsA) (4). Objectives: This is the first data on FOI in RA and PsA patients in clinical remission. The objective was to evaluate FOI as a method to detect subclinical disease activity in these patients. Methods: Admission criteria of this prospective study was patient or physician global assessment of disease activity of 10% or less on a visual analogue scale (VAS 0-10), thus resulting in the inclusion of 113 consecutive patients into the inception cohort. Admitted patients received a clinical examination by an independent investigator, and blood samples were taken for measurement of systemic inflammation (ESR, CRP). With these data, patients in DAS28 remission (DAS28 <2.6), SDAI remission (SDAI ≤3.3), CDAI remission (CDAI ≤2.8) and 2011 ACR/EULAR remission (Boolean based definition) were determined. Inflammatory activity in FOI was assessed by an experienced reader using the semiquantitative fluorescent optical imaging activity score (FOIAS) (3), which comprises of the measurement of joint-related fluorescent signal in an automatically generated composite image (Prima Vista Mode, PVM) and in three predefined phases of FOI (P1, P2, P3). Results: 78-87% of patients in remission showed remaining inflammatory activity in the PVM (table). Differences in the occurrence of inflammatory activity between the phases were significant to highly significant, with the lowest incidence of activity in P1 (20-28%). When excluding low signal enhancement and only regarding moderate to strong enhancement (≥2 on the semiquantitative score of 0-3), incidence of inflammatory activity was lower: 43% in PVM, 13% in P1, 78% in P2 and 17% in P3 for the DAS28 remission group. Comparing inflammatory activity in RA and PsA patients in DAS28 remission revealed no significant difference, though a clear trend towards more P1-activity in PsA patients could be observed (18% vs. 29% in RA and PsA patients, respectively). Conclusions: Frequency of subclinical disease activity observed in FOI is similar to that stated in MRI and US remission studies. Frequency of P1-activity in FOI is comparable to the reported frequency of power Doppler signal in patients with low disease activity or in remission (1), which is consistent with the previously established high agreement rates between P1 and power Doppler sonography (3). The prognostic value of subclinical FOI activity in remission patients is yet to be determined. References: Gandjbakhch F et al. Ann Rheum Dis2011 Dec;70(12):2159-62. Foltz V et al. Arthritis Rheum. 2012 Jan;64(1):67-76. Werner S et al. Ann Rheum Dis 2011;70, Online First, published on Oct. 12, 2011. Werner S et al. 2011 ACR/ARHP Annual Scientific Meeting, Chicago, IL, Nov. 4-9, 2011, Poster 199 Disclosure of Interest: F. Spiecker: None Declared, S. Werner Grant/Research support from: Pfizer, C. Hermsen: None Declared, M. Bahner Shareholder of: mivenion GmbH, M. Backhaus Grant/Research support from: Pfizer, H.-E. Langer Grant/Research support from: Pfizer